Integrating Basic Job Skills, OHS, and Word Culture Learning with Android Technology in Building Design Programs - Aura Amina Putri; Laras Oktavia Andreas; Henny Yustisia; Fani Keprila Prima (Journal of Practice Learning and Educational Development, 2026)
This research aims to develop Android-based learning media for the Basic Job Skills, Occupational Health and Safety (OHS), and Work Culture elements in the Building Design and Information Construction (DPIB) field at SMK Negeri 1 Pariaman. The development was driven by the need for interactive, attractive, and easily accessible learning innovations to support students in understanding vocational materials more contextually. This study used a Research and Development approach with the DDDE model, consisting of the decide, design, develop, and evaluate stages. Data were obtained using validation and practicality questionnaires assessed by media experts, material experts, teachers, and students. The validation results showed that the media achieved an Aiken's V score of 0.88 from media experts and 0.91 from material experts, indicating a very valid category. Practicality testing obtained 96 percent from teachers and 89 percent from students, which were categorized as very practical. Based on the findings, the developed Android-based learning media is suitable for use as an interactive, innovative, and effective learning resource to support the DPIB learning process in vocational schools.